Role of specific interventions to prevent stunting in children under five years in the first thousand days of life - Wiyono, Sugeng; Rachmat, Moch; Marbun , Rosmida M.; Karina, Sa’diah Multi; ., Meilinasari; Amrihati, Endang Titi; ., Muntikah; Miswaty, Titik Ceriyani (International Journal Of Community Medicine And Public Health, 2023)
Background: Indonesia faces the problem of stunting in children under five years by 24.4%. Boys aged 3 years with severe stunting have 15.0 points lower reading ability and girls have 11.0 points compared to mild stunting, resulting in a decrease in intelligence (IQ), so that learning achievement becomes low. Objective was to obtain information on the role of specific interventions to prevent stunting in children under five years in the first thousand days of life. Methods: Case-control design analytical research, in the stunted locus area, Jagakarsa Subdistrict, South Jakarta, Special area of the capital Jakarta Indonesia from 1 to 30 September 2021. Case samples of all stunting in children under five years and controls were normal height children who were matched for age and sex with 28 children each. The inclusion criteria in this research were ages 6-59 while the exclusion criteria in this research were toddler who had physical disabilities. Results: Variables that showed a significant relationship with stunting in children under five years (p<0.05) were the length of a baby at birth (p=0.005) OR 4.958 (95%CI: 1.529-15.987), maternal height (0.002) OR 5.727 (95%CI: 1.765-18.507), father’s education p=0.006 OR 5.169 (95%CI:1.520-17.580, and family income (p=0.012) OR 9.800 (95%CI: 1.116-86.041. Conclusions: Babies born <48.0 cm are at risk of 12.306 times of becoming stunting after controlling for variables such as maternal height, father’s education, energy intake, protein, iron, colds, exclusive breastfeeding, supplementary feeding for pregnant women and children and early initiation of breastfeeding.